Інструменти профорієнтаційної роботи зі старшокласниками: від гейміфікації до менторства - Гунчак, Олександр,Тетяна Равлюк (My University, 2025)
The article explores innovative approaches to career guidance for high school students amid dynamic changes in the labor market and the growing need to develop young people’s ability for flexible professional self-determination. The relevance of the topic lies in understanding self-determination as a systemic and dynamic process, as well as an essential component of life path design within the concept of lifelong learning. A crucial condition for the individualization and effectiveness of career guidance is professional diagnostics aimed at identifying learners’ aptitudes, interests, and readiness for informed choice. However, traditional methods such as lectures and conversations are insufficient for ensuring adaptability and flexibility in modern conditions. The contemporary educational context requires innovative and interactive methods, among which gamification and mentorship play a particularly important role. The article analyzes the essence of gamification as a powerful tool for simulating complex professional situations that foster critical thinking and enhance flexible response to challenges. In contrast, mentorship ensures a direct, personalized connection between students and the real labor market, facilitating the transfer of practical experience. This approach helps high school students develop realistic perceptions of their chosen field, cultivate soft skills, and build adaptability through observing dynamic changes within industries. The empirical foundation supporting the need to strengthen these approaches is based on the results of a nationwide monitoring study on career guidance in general secondary education institutions, conducted by the State Scientific Institution “Institute of Educational Analytics” under the auspices of the Ministry of Education and Science of Ukraine. The findings indicate that traditional methods show limited potential in developing self-awareness and flexibility, while career guidance activities lack systemic integration. Gamification and mentorship emerge as strategic responses to systemic challenges and key factors in forming a conscious and adaptive professional identity.
Keywords: career guidance, professional self-determination, professional diagnostics, gamification, mentorship, soft skills